Study of duration larvae stage bagworm (lepidoptera:psychidae) on michelia champaca trees in ex-situ and in-situ rearing and its species identification - Nur Alyani, bt Badrol Hisham (Universiti Malaysia Sarawak, UNIMAS, 2012)
Michelia champaca trees are dominant landscape trees that were planted in FRST, UNIMAS. However, bagworms attack create unhealthy landscape environment especially to the tree that were planted as ornamental plants. The most damaging stages of bagworms life stages were identified to be the larvae stage. In-situ rearing and ex-situ rearing were conducted to study the duration of the larvae bagworms. Ex-situ rearing showed larvae of bagworm only can survive for four weeks. While, in-situ rearing showed duration of bagworms of larvae depend on the tree condition. If the tree was not in the good condition the bagworms survival will slowly vanished after three weeks. Vice versa, if the tree was in good condition bagworms larvae could survived until three months. For species identification, pupae were used in species identifications. Based on the key of pupae identifations, bagworms that attack Michelia champaca trees at FRST, UNIMAS were identified to be Metisa plana species.